Optimizing the injection parameter of water atomised SS316L powder with design of experiment method for best sintered density - Jamaludin, Khairur Rijal; Muhamad, Norhamidi; Ab. Rahman, Mohd N.; Ahmad, Sufizar; Ibrahim, Mohd H.I.; Nor, Nor H.M. (University of Chiang Mai, 2009)
Injection moulding parameters that simultaneously satisfy green part qualities (green defect, green strength and green density) have been optimised using L27 (313) Taguchi orthogonal array. Moulding variables involved in the optimisation are the moulding pressure, moulding temperature, mould temperature, holding pressure, moulding rate, holding time and cooling time. The analysis of variance (ANOVA) is employed to determine the significant levels (a) and contributions of the variables to the green qualities. Results show that the mould temperature and holding time is highly significant simultaneously to the green qualities, while the holding pressure and cooling time does not show any significance. Besides that, densification of the compact moulded with the optimised moulding parameter is presented in this paper. With sintering temperature ranging from 1,340 to 1,400oC while heating rate and dwell time remains at 10oC/min and 4 hours respectively demonstrates that the optimised moulding parameter is enabled to produce a sintered part with a density which is very close to the solid density of SS316L.